2015
DOI: 10.4148/2378-5977.1123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pellet and Meal Feeding Regimens on Finishing Pig Performance, Stomach Morphology, Carcass Characteristics, and Economics

Abstract: A total of 2,100 pigs (PIC 327 × 1050, initially 68.8 lb) were used in a 118-d trial to determine the effects of pellet feeding regimens on finishing pig growth performance, stomach morphology, and carcass characteristics. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 6 dietary treatments (14 pens/treatment with 25 pigs/pen). Pens were sorted by gender allowing for 7 barrow and 7 gilt pens/treatment. The same corn-soybean meal-based diets containing 15% dried distillers grains with sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…Wondra et al (1995) fed mash and pelleted diets and had a 4 to 6% improvement in ADG in pigs fed pelleted diets. De Jong et al (2016) observed pigs fed meal had the greatest ADFI, whereas pigs fed pellets had the lowest. Additionally, pigs fed pelleted diets throughout had the greatest G:F, whereas pigs fed meal were least efficient.…”
Section: Nursery Pigsmentioning
confidence: 76%
See 1 more Smart Citation
“…Wondra et al (1995) fed mash and pelleted diets and had a 4 to 6% improvement in ADG in pigs fed pelleted diets. De Jong et al (2016) observed pigs fed meal had the greatest ADFI, whereas pigs fed pellets had the lowest. Additionally, pigs fed pelleted diets throughout had the greatest G:F, whereas pigs fed meal were least efficient.…”
Section: Nursery Pigsmentioning
confidence: 76%
“…Many researchers have found no differences in carcass characteristics when compared to pigs fed meal diets (Paulk and Hancock 2015;Nemechek et al, 2016;De Jong et al, 2016). However, Potter et al (2010 found that pigs fed pelleted diets had better gain efficiency, heavier market weight, and heavier carcass weights when compared to pigs fed meal diets.…”
Section: Carcass Characteristicmentioning
confidence: 99%
“…Furthermore, these observations are similar to those of Wondra et al (1995) and Regina et al (1999), who reported increased incidence of ulceration in the stomach of pigs fed pelleted diets. DeJong et al (2016) and Mösseler et al (2012) attributed this increased incidence of ulceration in pelleted diets to finer dietary particle size, resulting in a more liquid digesta and homogenous pH. However, Ayles et al (1999) reported that particle size did not influence the incidence of gastric ulcers, but severity was modulated by gastric tissue melatonin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding pigs with finely ground feeds was associated with a higher incidence of ulcers in such herds [ 52 - 54 ]. Other studies showed feeding pigs with pelleted feeds was also associated with a higher incidence of ulcers [ 10 , 18 , 24 , 43 , 54 , 55 , 56 ]. Feed restriction for economic reasons or as a feeding practice was suggested as a possible stress factor resulting from lower dietary fiber and resulting in gastric ulceration in some studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%